Buckling of composite shells with a novel initial imperfection model subjected to hydrostatic pressure. (1st October 2022) - Zhang, Xinhu; Li, Zhun; Yang, Zhaoqi; Jiang, Leilei; Pan, Guang
Abstract: The buckling problems of composite shells with initial imperfections under hydrostatic pressure are studied in this paper. A novel initial imperfection model is introduced. The analytical solutions of critical buckling pressures for composite shells both with and without the initial imperfection are derived based on the Sanders-type kinematic relations, respectively. The analytical results are compared with published experimental results and finite element (FE) results and agree well. The numerical examples are presented and the effects of initial imperfection parameters and ply angle as well as stacking sequence on the critical buckling pressures of composite shells are discussed. The results show that if the initial imperfection parameters are properly controlled, the critical buckling pressure can be dramatically improved. This could be valuable for the practical design of composite pressure hulls of an underwater vehicle.